High dynamic range diamond detector acquisition system for beam wire scanner applications. (3rd March 2016) - Sirvent, J.L.; Dehning, B.; Piselli, E.; Emery, J.; Dieguez, A.
Abstract: The CERN Beam Instrumentation group has been working during the last years on the beam wire scanners upgrade to cope up with the increasing requirements of CERN experiments. These devices are used to measure the beam profile by crossing a thin wire through a circulating beam, the resulting secondary particles produced from beam/wire interaction are detected and correlated with the wire position to reconstruct the beam profile. The upgraded secondary particles acquisition electronics will use polycrystalline chemical vapour deposition (pCVD) diamond detectors for particle shower measurements, with low noise acquisitions performed on the tunnel, near the detector. The digital data is transmitted to the surface through an optical link with the GBT protocol. Two integrator ASICs (ICECAL and QIE10) are being characterized and compared for detector readout with the complete acquisition chain prototype. This contribution presents the project status, the QIE10 front-end performance and the first measurements with the complete acquisition system prototype. In addition, diamond detector signals from particle showers generated by an operational beam wire scanner are analysed and compared with an operational system.